2017
DOI: 10.1002/eji.201646841
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic dilemmas in HLH: Can T‐cell phenotyping help?

Abstract: The diagnosis of hemophagocytic lymphohistiocytosis (HLH) can be a difficult one, and the distinction between primary versus secondary HLH can be particularly challenging during the early stages of diagnosis. This distinction is important to make as primary HLH requires allogeneic hematopoietic cell transplantation for a definitive cure. Flow cytometric screening tests for many of the genetic forms of HLH are available. However, not all patients with primary HLH are captured by these screening tests, due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…T cell populations were activated markedly and effector-differentiated in primary HLH, while this signature was mainly absent in patients with secondary HLH. T cell activation in virus-associated secondary HLH was situated between the spectrum from non-virus-associated secondary HLH to primary HLH [21,22]. Thus, in contrast with primary HLH, T cells do not appear to play a similar, dominant pathogenic role in secondary HLH, demonstrating that disease is not driven necessarily by over-activation of the adaptive immune system.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…T cell populations were activated markedly and effector-differentiated in primary HLH, while this signature was mainly absent in patients with secondary HLH. T cell activation in virus-associated secondary HLH was situated between the spectrum from non-virus-associated secondary HLH to primary HLH [21,22]. Thus, in contrast with primary HLH, T cells do not appear to play a similar, dominant pathogenic role in secondary HLH, demonstrating that disease is not driven necessarily by over-activation of the adaptive immune system.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, combined targeting of CD4 1 and CD8 1 T cells indicated that T cells were not required for disease pathogenesis, while functional T and B cells were dispensable to induce HLH-like disease in MCMV-infected SCID mice. T cell activation in virus-associated secondary HLH was situated between the spectrum from non-virus-associated secondary HLH to primary HLH [21,22]. In a CpG-induced model of macrophage activation syndrome (MAS), mice lacking T, B and NK T cells could still develop HLH [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations